Pandangan Al-Buthi Terhadap Hukum Mengikuti Program Keluarga Berencana (KB) Berdasarkan Intervensi Negara - Moh. Mufid (AL-HUKAMA, 2020)
This article aims to discuss al-Buthi's thoughts about the law following a family planning program on state intervention. The family planning program is claimed as one of the strategies to reduce birth rates to avoid high population growth rates. On the other hand, one of the aims of marriage in Islam is to give birth to offspring who can be the successor and prosperity of the earth. Therefore, family planning programs in this context are seen as blocking this noble goal. Al-Buthi, one of the contemporary scholars, has a very dichotomous thought. This study shows that al-Buthi is of the view that family planning law over state intervention for his people is an act that is not in line with the purpose of marriage. That is why, according to al-Buthi the law is haram. Unlike the law, if both husband and wife couples carry out family planning programs through azl or other contraceptives without any intervention from any party, including from the state, then it is permissible as long as the husband and wife's consent and the existence of benefits that are personal to both. The basic thought of al-Buthi is the qiyasi reasoning and the maqasidi reasoning.